Odpowiedź :
[tex]a)\\|x|=5\\x=5\\x=-5\\b) \\|x-4|=2\\x-4=2 /+4\\x=6\\\\-(x-4)=2\\-x+4=2\\-x=2-4\\-x=-2\\x=2\\\\c) \\|x-3|=1\\x-3=1 /+3\\x=4\\\\-(x-3)=1\\-x+3=1\\-x=1-3\\-x=-2\\x=2\\\\d) \\|x-2|=3\\x-2=3\\x=3+2\\x=5\\\\-(x-2)=3\\-x+2=3\\-x=3-2\\-x=1\\x=-1\\\\e) \\|x-1|=0\\x-1=0\\x=0+1\\x=1\\[/tex]
[tex]-(x-1)=0\\-x+1=0\\-x=-1\\x=1\\\\f) \\|x+2|=4\\x+2=4 /-2\\x=2\\\\-(x+2)=4\\-x-2=4\\-x=4+2\\-x=6\\x=-6\\\\g) \\|x+3|=-1\\\text{Brak rozwiazan - wartosc bezwzgledna jest zawsze nieujemna}\\\\h)\\|x+4|=2\\x+4=2 \\x=2-4\\x=-2\\\\-(x+4)=2\\-x-4=2\\-x=2+4\\-x=6\\x=-6[/tex]